2013
DOI: 10.1371/journal.pone.0056864
|View full text |Cite
|
Sign up to set email alerts
|

High Serum Uric Acid and Increased Risk of Type 2 Diabetes: A Systemic Review and Meta-Analysis of Prospective Cohort Studies

Abstract: ObjectiveCurrent evidence suggests high serum uric acid may increase the risk of type 2 diabetes, but the association is still uncertain. The aim of the study was to evaluate the association between serum uric acid and future risk of type 2 diabetes by conducting a meta-analysis of prospective cohort studies.Design and MethodsWe conducted a systematic literature search of the PubMed database through April 2012. Prospective cohort studies were included in meta-analysis that reported the multivariate adjusted re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
215
1
8

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 286 publications
(237 citation statements)
references
References 35 publications
(56 reference statements)
13
215
1
8
Order By: Relevance
“…31 Our study results are consistent with that there was a significant rise in blood sugar levels as depicted in Tables 2 and 3. There are reported studies suggesting increased uric acid levels are associated with alteration in lipid levels and positively correlated to hypertriglyceridemia, hypercholesterolemia and increased arterial tone, whereas HDL levels were inversely correlated with serum uric acid levels. 32,33 In our study there was slight elevation triglycerides and total cholesterol but values were not statistically significant as compared to control group.…”
supporting
confidence: 92%
“…31 Our study results are consistent with that there was a significant rise in blood sugar levels as depicted in Tables 2 and 3. There are reported studies suggesting increased uric acid levels are associated with alteration in lipid levels and positively correlated to hypertriglyceridemia, hypercholesterolemia and increased arterial tone, whereas HDL levels were inversely correlated with serum uric acid levels. 32,33 In our study there was slight elevation triglycerides and total cholesterol but values were not statistically significant as compared to control group.…”
supporting
confidence: 92%
“…Sirota et al [33] revealed that increased serum uric acid levels are associated with greater severity of NAFLD by ultrasonography. Several prospective and retrospective studies have also provided evidences supporting the association of high serum uric acid, the risk of T2DM, cardiovascular diseases and hepatitis [34][35][36] . These have further supported that NAFLD is the hepatic manifestation of MetS.…”
Section: Metabolic Pathwaysmentioning
confidence: 93%
“…Since NAFLD is a hepatic manifestation closely related to elevated levels of SUA and insulin resistance, this association has been studied in several studies among T2DM subjects. 12,13 Compared with non diabetic subjects, T2DM are believed to have an increased risk of developing NAFLD, but the true prevalence of the disorder among prediabetic subjects has not been systematically assessed. In addition, so far, population-based data to determine whether SUA and insulin resistance levels are associated with NAFLD in different stages of impaired glucose regulation, in particular prediabetic states, is scarce.…”
Section: Introductionmentioning
confidence: 99%